Troubling whiteness: A critical autoethnographic exploration of being white in the context of calls for the decolonization of higher education - Frizelle, Kerry (PINS-Psychology in Society, 2019)
The context of higher education in South Africa continues to be a racialised space despite its transition from Apartheid to democracy in 1994. This article reports on a critical autoethnographic study that uses reflexive memory work to explore how the author can continue to position herself and practice as an educator within this current context of higher education. The central argument of the paper is that complex forms of identity politics and white fragility heighten a tendency for white people to respond with ‘injurious’ self-defensiveness when their whiteness is called out. Such responses are counter-productive to finding constructive ways of positioning oneself as a white person in the ongoing and wider project of decolonising higher education in South Africa. A process of critical reflectivity, mediated by a range of theoretical insights, enabled the author to work with her own white fragility and move beyond a limited defensiveness towards a position that allowed her to acknowledge her on-going whiteness while envisioning more constructive ways of being a white educator in the current South African context.